Optimisation of a micro‐neutralisation assay and its application in antigenic characterisation of influenza viruses. Issue 6 (November 2015) - Lin, Yipu; Gu, Yan; Wharton, Stephen A.; Whittaker, Lynne; Gregory, Victoria; Li, Xiaoyan; Metin, Simon; Cattle, Nicholas; Daniels, Rodney S.; Hay, Alan J.; McCauley, John W.
<x xml:space="preserve">Abstract</x> Objectives The identification of antigenic variants and the selection of influenza viruses for vaccine production are based largely on antigenic characterisation of the haemagglutinin (HA) of circulating viruses using the haemagglutination inhibition (HI) assay. However, in addition to evolution related to escape from host immunity, variants emerging as a result of propagation in different cell substrates can complicate the interpretation of HI results. The objective was to develop further a micro‐neutralisation (MN) assay to complement the HI assay in antigenic characterisation of influenza viruses to assess the emergence of new antigenic variants and reinforce the selection of vaccine viruses. Design and setting A 96‐well‐plate plaque reduction MN assay based on the measurement of infected cell population using a simple imaging technique. Sample Representative influenza A (H1N1) pdm09, A(H3N2) and B viruses isolated between 2004 and 2013 Main outcome measures and results Improvements to the plaque reduction MN assay included selection of the most suitable cell line according to virus type or subtype, and optimisation of experimental design and data quantitation. Comparisons of the results of MN and HI assays showed the importance of complementary data in determining the true antigenic relationships among recent human influenza A(H1N1)pdm09, A(H3N2) and type B viruses. Conclusions Our study demonstrates that the improved MN assay has certain advantages over the HI assay: it is not significantly influenced by the cell‐selected amino acid substitutions in the neuraminidase (NA) of A(H3N2) viruses, and it is particularly useful for antigenic characterisation of viruses which either grow to low HA titre and/or undergo an abortive infection resulting in an inability to form plaques in cultured cells.